GEOPOETICS IN BACHELARD AND WUNENBURGER: AN ESSAY ON AN ANTHROPOLOGIST IN THE PHILOSOPHY OF SPACE - da Rocha, Gabriel Kafure (Revista Inter-Legere, 2018)
This essay is an exercise of trying to conform the philosophy of Gaston Bachelard and Jean-Jacques Wunenburger in a perspective of the Amerindian thought, in which the imaginary of autochthonous stories can be reread through the geopoetic structures of both thinkers. The title "an essay on an anthropologist" does not refers directly to Wunenburger as an anthropologist of the imaginary, neither to Bachelard as a philosopher of space. Our intention with the subtitle is to create an anthropological character that geopoetically experiences its relationship with the world. To accomplish this, we make use of the books: “Earth and reveries of will” by Bachelard and “L’imagination géopoïétique” by Wunenburger. Keywords: Imaginary. Spatiality. Amerindian thought.